2012
DOI: 10.1128/cmr.00012-12
|View full text |Cite
|
Sign up to set email alerts
|

Human and Animal Dirofilariasis: the Emergence of a Zoonotic Mosaic

Abstract: SUMMARY Dirofilariasis represents a zoonotic mosaic, which includes two main filarial species ( Dirofilaria immitis and D. repens ) that have adapted to canine, feline, and human hosts with distinct biological and clinical implications. At the same time, both D. immitis and D. repens are themselves hosts to symbiotic bacteria of the genus Wolbachia , the study of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
892
3
36

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(945 citation statements)
references
References 320 publications
(380 reference statements)
14
892
3
36
Order By: Relevance
“…Dirofilaria are parasitic roundworms infecting certain mammals by way of mosquito vectors including Ae. aegypti (Simón et al., 2012). 18S rRNA sequences resembling Dirofilaria were also recovered from the same pool, although the sequence was not of sufficient quality to be represented in the final taxon list (data not shown, but Dirofilaria sp.…”
Section: Resultsmentioning
confidence: 99%
“…Dirofilaria are parasitic roundworms infecting certain mammals by way of mosquito vectors including Ae. aegypti (Simón et al., 2012). 18S rRNA sequences resembling Dirofilaria were also recovered from the same pool, although the sequence was not of sufficient quality to be represented in the final taxon list (data not shown, but Dirofilaria sp.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of human cases are attributed to Dirofilaria repens, a mosquito transmitted filarial nematode, which causes subcutaneous dirofilariosis in dogs, cats and wild canids (Simón et al 2012). It has been shown not only that infection rates are increasing in well-known endemic areas in southern Europe, but also that the disease is spreading towards northern and eastern areas formerly free of the infection (Genchi et al 2011, Tasić-Otašević et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…pipiens, allowing it to use almost any kind of water collection as breeding site, and having a very broad period of seasonal activity. Changes in seasonal vector densities are likely to impact the rate of infection as previously described by Simón et al (2012) and several models for the transmission periods have been proposed based on DDU (Dirofilaria development units) . In fact, it has been shown that Spain is the European Union country with the longest transmission period for Dirofilaria .…”
Section: Discussionmentioning
confidence: 99%
“…Filarioid nematode parasites affect millions of people and animals worldwide, and represent a major health hazard with significant economic implications (Laaksonen et al, 2010). Canine dirofilariosis is a major veterinary health problem in tropical, subtropical and temperate regions of the world (Simón et al, 2012), with at least 70 species of mosquitoes being considered as potential vectors . Dirofilariosis is endemic in the Mediterranean region, affecting southern European countries including Portugal, Spain, France and Italy (Genchi et al, 2005 andMorchón et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation